Co-occurrence of risk factors for cardiovascular disease by social class: 1958 British birth cohort. Issue 12 (13th November 2008) - Power, C; Atherton, K; Manor, O
Abstract : Aim: To establish whether social differences in multiple risk factors for cardiovascular disease are due to a greater strength of association (higher correlation) between risk factors in less advantaged groups. Methods: Co-occurrence of five risk factors (smoking, hypertension, low high-density lipoprotein cholesterol, obesity, diabetes) in 3614 British 45-year-old men and 3560 women in the manual and non-manual social groups. Results: 4.0% of women in manual groups had ⩾3 risk factors compared with 1.7% in non-manual groups: 6.2% and 3.4% respectively for men. There was a higher than expected percentage of the population, overall, with ⩾3 risk factors assuming independence between risk factors; correspondingly, there was a slightly lower than expected proportion with one factor. However, patterns of observed to expected ratios were consistent in manual and non-manual groups and did not differ by the number of risk factors. Conclusions: Higher prevalence of multiple risk factors in manual groups was due to the higher prevalence of individual factors rather than a greater tendency of those with an individual risk factor to have additional risks. Strategies to reduce multiple risk factors in less advantaged groups would help to lessen their health burden.